2019
DOI: 10.1177/0022034519827566
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Dental Restoration Survival: A Practice-Based Study

Abstract: To improve patient dental care, it is necessary to identify possible risk factors for the failing of restorations. This practice-based cohort study investigated the performance and influence of possible risk factors at the level of the practice, patient, tooth, and restoration on survival of direct class II restorations. Electronic patient files from 11 Dutch general practices were collected, and 31,472 restorations placed between January 2015 and October 2017 were analyzed. Kaplan-Meier statistics were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 28 publications
4
37
0
4
Order By: Relevance
“…(3) Most RCTs included not only class II restorations placed due to primary caries, but also replacement restorations of failed fillings, which are probably larger and more likely to fail (again) than newly placed restorations. A recent study [59] also showed that restorations placed due to caries were less prone to fail than restorations placed due to fracture. In view of this, survival of class II restorations for cavitated proximal caries lesions might be even slightly better than demonstrated in the present review.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(3) Most RCTs included not only class II restorations placed due to primary caries, but also replacement restorations of failed fillings, which are probably larger and more likely to fail (again) than newly placed restorations. A recent study [59] also showed that restorations placed due to caries were less prone to fail than restorations placed due to fracture. In view of this, survival of class II restorations for cavitated proximal caries lesions might be even slightly better than demonstrated in the present review.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, some of the RCTs reported on restorative materials that are no longer available, which also limits the validity of this meta-review. (2) Survival of restorations depends on various patient-related risk factors [59][60][61] which were not addressed in this meta-review. Only about a quarter of the RCTs assessed the caries risk of the patients as, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the human oral environment is more complicated than the in vitro experimental context because the oral cavity temperature, food intake, and the pH and composition of saliva vary between subjects and even within a subject [ 43 ]. In addition, the mechanical properties and material stability of the coating layer were not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are some initiatives proposing pragmatic trials in the context of PBRN. One good example is the ongoing trial in the Dutch PBRN, 34 which aims to investigate the effectiveness of antimicrobial containing dental adhesives for the prevention of secondary caries. For this study, a cohort of dental practices with motivation to participate and that are acknowledged for keeping very good dental records were invited to take part in the study.…”
Section: Experimental Studies -From Explanatory Rct's To Pragmatic Trmentioning
confidence: 99%